2011
DOI: 10.1002/adfm.201101013
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Photoluminescence of CaHfO3 and SrHfO3 Nanoparticles

Abstract: This article reports on optical properties of SrHfO3 and CaHfO3 nanoparticles with sizes as small as 1.6 nm, synthesized via non aqueous sol–gel routs for the first time. An unexpectedly strong luminescence from the undoped nanoparticles was observed in the visible spectrum over a wide temperature range, also exhibiting sensitivity to temperature variation and surrounding ambient (vacuum/air) and exposure time to UV light. A tentative model is proposed to explain these phenomena in terms of luminescent centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…This further expedites the development and integration of new technologies based on HfO 2 owing to already existing technological platforms. Major efforts are being directed worldwide towards mastering the dimensionality of nanoparticles; among established methods ensuring control of both size and shape is the nonaqueous sol–gel route [ 18 19 ]. In our previous studies, a strong photoluminescence in the visible range was observed from HfO 2 nanoparticles under below-bandgap excitation [ 20 21 ] and attributed to surface-located intrinsic and extrinsic defects arising from Hf 3+ and O 2− vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…This further expedites the development and integration of new technologies based on HfO 2 owing to already existing technological platforms. Major efforts are being directed worldwide towards mastering the dimensionality of nanoparticles; among established methods ensuring control of both size and shape is the nonaqueous sol–gel route [ 18 19 ]. In our previous studies, a strong photoluminescence in the visible range was observed from HfO 2 nanoparticles under below-bandgap excitation [ 20 21 ] and attributed to surface-located intrinsic and extrinsic defects arising from Hf 3+ and O 2− vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by this, we performed a systematic study on the emission property of the Ce 3+ ion doped CaHfO 3 which is a counterpart of CaZrO 3 . Actually, CaHfO 3 has been intensively studied as a useful electronic and optical material By using the photoluminescence (PL) spectroscopy, we observed a strong emission near 430 nm which should originate from 5d‐4f transitions. This violet‐blue emission was maximized with doping of 0.5% Ce 3+ concentration.…”
Section: Introductionmentioning
confidence: 82%
“…Silver microparticles synthesis The synthesis of Ag microparticles is based on the non-hydrolytic sol-gel method [18,19] that has been recently applied for the synthesis of Ag antimicrobial coatings [20,21]. Briefly, 642 mg of silver acetate (99%, Aldrich) along with 20 cm 3 of benzylamine (99%, Aldrich) were used for the synthesis of the particles.…”
Section: Methodsmentioning
confidence: 99%